Perception-action and adaptation in postural control of children and adolescents with cerebral palsy - Barela, Jose A. [UNESP]; Focks, Grietje M. Jaspers; Hilgeholt, Toke; Barela, Ana M. F.; Carvalho, Raquel de P.; Savelsbergh, Geert J. P. (Pergamon-Elsevier B.V. Ltd, 2011)
The aim of this study was to examine the coupling between visual information and body sway and the adaptation in this coupling of individuals with cerebral palsy (CP). Fifteen children with and 15 without CP. 6-15 years old, were required to stand upright inside of a moving room. All children first performed two trials with no movement of the room and eyes open or closed, then four trials in which the room oscillated at 0.2 or 0.5 Hz (peak velocity of 0.6 cm/s), one trial in which the room oscillated at 0.2 Hz (peak velocity of 3.5 cm/s), and finally two other trials in which the room oscillated again at 0.2 Hz (peak velocity of 0.6 cm/s). Participants with CP coupled body sway to visual information provided by the moving room, comparable to the coupling of participants without CP. However, participants with CP exhibited larger body sway in maintaining upright position and more variable sway when body sway was induced by visual manipulation. They showed adaptive sensory motor coupling, e.g. down-weighting visual influence when a larger stimulus was provided, but not with the same magnitude as typically developing participants. This indicates that participants with CP have less capability of adaptation. (C) 2011 Published by Elsevier Ltd.
Keywords: Vision; Cerebral palsy; Adaptation; Sensory re-weighting; Posture